THE EFFECTIVENESS USING PICTURE AND CARD MEDIA IN TEACHING ENGLISHTO INCREASE STUDENTS’ VOCABULARY AT ELEVENTH GRADE AT SMAN 3 TOLITOLI - Hidayati Hidayati (Jurnal Madako Education, 2022)
This research aimed to find out whether picture and card media are effective and to compare which media is more effective to increase students’ vocabulary. This research is true-experimental research design. The samples were 10 students at class VIII IIS 1 and class VIII IIS 2 which selected randomly. Data collected through giving pre-test and post-test. The pre-test conducted to measure the students’ knowledge before giving the treatment, whereas the post-test accomplished to evaluate and to measure their ability and knowledge after giving the treatment. Those data analyzed statistically. In the card media group, the mean score of post-test is 75,04 was higher than pre-test 48,12 and the mean score of post-test in picture group is 84,84 was higher than pre-test 38,76. The t-counted value is higher than the t-table. f =7,529 > = 2,306 It means that the hypothesis of the research is accepted. In other words, using picture and card media in teaching English is effective to increase students’ vocabulary. Based on the result of pre-test and post-test in two media, it can be concluded that the picture media is more effective than card media in teaching English to increase students’ vocabulary especially on verb.